Meanwhile, Rehearsals - Cheng, Samantha (Auckland University of Technology, 2021)
This practice-based research examines the role of failure in art making through a series of art works that attempt to fail by: never beginning, self-censoring, pursuing purposelessness, never being ready, or devising ways to ensure irresolution. In doing this the project reconceives of failure as a generative space: a meanwhile that allows for self-censorship, avoiding failure, conducting only rehearsals, performative gestures, and deferring decision making. In engaging strategies of humour, it uses the notions of rehearsing and stalling as devices that ensure we never arrive at a point of conclusion. This offers a framework for understanding the many ways a project can fail (or attempt to fail) and through a series of performative gestures, seek to challenge failure and the fear it elicits. In doing so it comes to understand that art making is as much about its limits as its potential.
Keywords: Failure; Futility; Humour; Absurdity; Performance; Performativity; Installation; Uncertainty